Evaluation of fungicides against false smut disease of rice (Oryza sativa L.): Evaluation of fungicides against false smut disease of rice - Gangwar, Dr Rakesh Kumar; Thorat, Sanju Bhai Soma Bhai; Kacha, Ravjibhai Parshottambhai; Parmar, Dr M.B. (ORYZA-An International Journal of Rice, 2024)
False smut of rice caused by Ustilaginoidea virens is a worldwide serious disease of rice. Seven fungicides were evaluated against false smut disease of rice during kharif, 2019 and 2020 at two locations. The ready mix fungicide azoxystrobin 18.2 % + difenoconazole 11.4% w/w SC was used in three doses where as other fungicides were used in single dose. Total two fungicidal sprays were given, first at 50% flowering and second at 100% flowering stage. The results showed that tebuconazole 50% + trifloxystrobin 25% WG at 0.8 g/L and picoxystrobin 7.05% + propiconazole 11.7% SC at 2.0 ml/L were found best in order of efficacy against false smut. These treatments recorded minimum per cent infected panicles/ sq m (3.57 and 4.31, respectively), per cent infected spikelets/ panicle (4.58 and 4.66, respectively) and maximum grain (7114 and 7043 kg/ha, respectively) and straw yield (10942 and 10984 kg/ha, respectively). The next best performance was recorded in azoxystrobin 18.2 % + difenoconazole 11.4% w/w SC at 1.25 ml/L where per cent infected panicle/ sq m was 6.50, per cent infected spikelets/ panicle was 8.22, where as the grain and straw yield was 6410 and 10551 kg/ha, respectively.